Financial system stability vs. social policy - Karaś, Marta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper adds to the discussion of social costs of financial crises through theoretical elaboration, arguing for the position that supporting the stability of financial systems, if combined with public confidence in financial markets and banking, leads to a reduction of social costs by reducing the frequency of crises associated with the long-term development of the financial sphere in the world. Following the theoretical function proposed by Adrian, Covitz and Liang [2014], the author elaborates that prudential regulation may lower the social costs of crises. This calls for an active role of regulating the financial sector and that of the central banks, as the preferred sensitivity of the financial system to shocks may be achieved by prudential regulation and the increasing of transparency of the system, as well as by the management of social perception of stability (security) of this system. The paper postulates the abovementioned relation by reviewing selected empirical studies and framing the discussion in theoretical elaboration on social costs and financial stability
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 482, s. 85-106
Keywords: social costs; financial stability; financial crisis; macro-prudential regulation; koszty społeczne; stabilność finansowa; kryzys finansowy; regulacje makroostrożnościowe